A relação sociedade/divindades/natureza no templo Espírita de Umbanda Abaçá de Oxalá em Pato Branco - PR: modos plurais de existência - Favaro, Jean Filipe (2018)
Ethnographic research immersed in the context of the Third World explored different and diverse practices of thinking, brotherhood, experimenting and codifying biological and natural dimensions. Among the various social aggregates mobilized around the world through counter-hegemonic rationalities, Afro-Brazilian cults were announced as multiple religiosities of great ecological importance and with connections with the most diverse and contradictory actants of the cosmos. They resist in the Third World, with its decolonizing subjectivities that multiply in each place of worship. At this juncture, this research was carried out with the Spiritist Center of Umbanda Abaça de Oxalá, aiming to analyze the network that is formed in the interrelations between humans / divinities / nature. The Actor-Network Theory as presented by Latour (1994, 2004, 2012) provided tools for an ethnography appropriate to the reality of this terreiro to be elaborated, expanding the number of hidden actors who relate, act and speak. Thus, during the 19 month period, the research was operationalized by means of the Participatory Observer technique, based on field diary annotations, photographs, transcripts of interviews and drawings. The form of the records was developed in the documentary analysis, through the annotations in the material analyzed. The aiming was to generate an actor-network account to unfold a greater number of actors, mediators and controversies that connect to the practices associated with the relations between human /divinities / nature in the Abaca de Oxalá. The humans that make up the place are characterized by the “pai de santo”, “filhos de corrente” and clients. They interact with the Orixás in different strata and levels of commitment to local norms, seeking spiritual favors from their subjective motivations, which include the spheres of health, affective-family issues, financial prosperity and spiritual development (in the case of filhos de corrente). The favors of the Orixás are obtained from a rich and complex regime of exchanges, which allows to place places of nature (points of force), natural elements (vegetation, minerals), food, fire, water, and multiple elements that are relative to the subjectivity of each human connected in the net, that emerge in the form of offerings, medicinal teas, herbal baths, smokes, etc. These exchanges are subsidized by a framework of knowledge about their natures, specificities, associations and actions. These knowledges are inseparable from doings, and their primary source is the Orixas. From these knowledge, it was possible to identify a total of 159 spiritual entities mobilized in the discourses and activities of the terreiro and 140 vegetables used for the most diverse purposes that humans need. The processing of ritualistic activities in the Afro-Brazilian religious context, refers to a complex reality engendered by the deep intersections between the spheres of the social, supernatural and natural world. The emic concept of energy proves substantial for such connections to emerge and act in the daily life of the terreiro, because the Orixá is energy and connects with the energy of humans and nature so that transformations in the real world are engendered.